Prototype Evaluation Of E-Knowledge Integration System: A Case Study In Small Medium Enterprises - Nur Ilyana Ismarau Tajuddin,; Rusli Abdullah,; Marzanah A. Jabar; Yusmadi Yah Jusoh (Universiti Sains Islam Malaysia, 2024)
Date: 9 September 2021 Platform: MSTeams, USIM Nilai, Negeri Sembilan, Malaysia.